"Explode into small pieces": Suicidal ideation among child sexual abuse survivors. (September 2022) - Tsur, Noga; Najjar, Afnan Attrash; Katz, Carmit
Abstract: Background: Child sexual abuse (CSA) has been acknowledged as predisposing survivors to an increased risk of suicidal ideation and attempts. Despite this risk being widely recognized, the study of suicidality has mainly focused on psychopathology, while less attention has been given to survivors' experiences and perceptions. Objective: This study aims to uncover the experiences and perceptions of suicidality among adult CSA survivors. Participants and settings: The sample consisted of 41 adult CSA survivors' written narratives of abuse that included references to suicide. Methods: Written narratives of CSA experiences were collected from 41 adult participants as part of the Israeli Independent Public Inquiry on CSA to change public policy. An inductive thematic analysis guided the exploration of the stories. Results: The findings portrayed several main themes regarding the survivors' experiences before, during and after suicidal thoughts and behaviors. These themes elucidated their motivations leading to suicidal attempts, including the wish to end one's self and suffering, self-blame, communicate the abuse and the request for recognition. Additionally, the survivors' stories illuminated their experiences following the suicidal attempts, depicting inadequate treatment and difficulties with the psychiatric labeling of a mental health disorder. Conclusions: The findings of this study uncover new insights regarding the link between trauma, posttraumatic suffering, and suicidality within a social interaction context. Furthermore, these findings call medical and psychosocial health practitioners to view post-CSA suffering as trauma-related rather than personal psychopathology and to adjust practices to adapt to survivors' experiences and needs.